Empagliflozin activates Sestrin2-mediated AMPK/mTOR pathway and ameliorates lipid accumulation in obesity-related nonalcoholic fatty liver disease - Ma, Yuting; Zhang, Guangdong; Kuang, Zenggguang; Xu, Qian; Ye, Tongtong; Li, Xue; Qu, Na; Han, Fang; Kan, Chengxia; Sun, Xiaodong (Frontiers in Pharmacology, 2022)
Empagliflozin (EMPA) therapy has led to improvements in patients with non-alcoholic fatty liver disease (NAFLD). Sestrin2 is a stress-inducible protein that controls the AMPK-mTOR pathway and inhibits oxidative damage in cells. This study investigated the functional implications of EMPA on the multifactorial pathogenesis of NAFLD and potential underlying molecular mechanisms of pathogenesis. An in vitro model of NAFLD was established by treating HepG2 cells with palmitic acid (PA); an in vivo model of NAFLD was generated by feeding C57BL/6 mice a high-fat diet. Investigations of morphology and lipid deposition in liver tissue were performed. Expression patterns of Sestrin2 and genes related to lipogenesis and inflammation were assessed by reverse transcription polymerase chain reaction. Protein levels of Sestrin2 and AMPK/mTOR pathway components were detected by Western blotting. NAFLD liver tissues and PA-stimulated HepG2 cells exhibited excessive lipid production and triglyceride secretion, along with upregulation of Sestrin2 and increased expression of lipogenesis-related genes. EMPA treatment reversed liver damage by upregulating Sestrin2 and activating the AMPK-mTOR pathway. Knockdown of Sestrin2 effectively increased lipogenesis and enhanced the mRNA expression levels of lipogenic and pro-inflammatory genes in PA-stimulated HepG2 cells; EMPA treatment did not affect these changes. Furthermore, Sestrin2 knockdown inhibited AMPK-mTOR signaling pathway activity. The upregulation of Sestrin2 after treatment with EMPA protects against lipid deposition-related metabolic disorders; it also inhibits lipogenesis and inflammation through activation of the AMPK-mTOR signaling pathway. These results suggest that Sestrin2 can be targeted by EMPA therapy to alleviate lipogenesis and inflammation in obesity-related NAFLD.